LEXICAL VARIATION IN THE CONCEPT OF 'FACE' ACROSS CONTEMPORARY LANGUAGE SYSTEMS: A COMPARATIVE STUDY OF UZBEK, ENGLISH, AND RUSSIAN LEXICONS - Niyazova Shoira Toirovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article embarks on a detailed contrastive analysis of the lexical significances attributed to the concept «face» in contemporary Uzbek, English, and Russian linguistic systems. Employing an intricate blend of semantic analysis, cultural linguistics, and comparative methodology, this study meticulously explores the lexico-semantic variances and cultural nuances embedded within this concept. While navigating the complex terrain of linguistic expression and cultural cognition, it reveals the distinct ways in which these three languages encapsulate socio-cultural perceptions and conceptualizations of «face». The research utilizes a comprehensive corpus-based approach, incorporating both qualitative and quantitative data analyses, to dissect the semantic fields and collocational networks associated with «face» in each language. This exploration not only highlights linguistic differences but also sheds light on the cultural contexts shaping these variances. Moreover, the study contributes to the broader discourse on cross-linguistic variability and universality in conceptual metaphors, providing insights into the cognitive mechanisms driving language use and comprehension across diverse linguistic communities. Consequently, this article not only bridges linguistic gaps but also enhances the understanding of the complex interplay between human language, cognition, and culture.